Characteristics of Patients With Chronic Kidney Disease: A Descriptive Study - Christian Ronald Tanggo; Nikita Agustina Losoh; Ani Oranda Panjaitan; Kezia Martina; Daniel Reinaldo Parsaoran Situmorang (CV. Inara, 2026)
Chronic Kidney Disease (CKD) is a major non-communicable disease with a high health burden both globally and nationally. This study aims to describe the clinical and demographic characteristics of CKD patients hospitalized at the Universitas Kristen Indonesia General Hospital in 2023. This research employed a quantitative descriptive design with a cross-sectional approach. A total of 82 patients were selected through total sampling from medical records. The collected data included age, sex, occupation, highest educational level, place of residence, and history of hypertension and diabetes mellitus as the main comorbidities. The results showed that the 55–65-year age group was the most prevalent (35.6%). Female patients dominated the sample (55.9%). Based on occupation, most patients were housewives (35.4%). The highest level of education recorded was senior high school (54.9%). The most common comorbidities were hypertension (43.9%) and diabetes mellitus (13.4%). These findings indicate that older age, female sex, non-formal occupations, senior high school education level, and the presence of hypertension and diabetes mellitus are frequently observed characteristics among CKD patients at RSU UKI in the 2023 period. The results are expected to serve as a baseline for developing prevention and clinical management strategies for CKD and to raise public awareness regarding the importance of regular kidney function screening.